Learning Organizational Culture in Greek Public Hospitals - Goula, Aspasia (Int J Environ Res Public Health, 2021)
(1) Background: A learning organizational culture is crucial to the safety of patients and the quality of public health care. The aim of this study was to assess the learning organizational culture and capacity of Greek public hospitals. (2) Materials and Methods: A cross-sectional analysis was carried out in six public general hospitals and stratified sampling was used as the sampling technique. A total of 480 questionnaires were distributed to health care professionals and 380 valid questionnaires were returned (78% response rate). The comprehensive form of the Dimensions of Learning Organization Questionnaire (DLOQ), which was adapted and translated into Greek, was used for data collection in this survey. (3) Results: The level of learning organizational culture and capacity in the health units are very low. All seven dimensions of the learning organizational instrument are lower than the theoretically neutral median (3.0). Health care employees believe that the hospital’s existing culture and management practices do not foster and contribute to continuing learning, which is the fundamental aspect of self-development, department development and performance improvement. (4) Conclusions: Greek public hospitals need to adopt different types of leadership practices and culture in order to be able to facilitate organizational learning. Organizational learning (OL) is based on collaborative working, a culture that encompasses learning as participation in the organizational work practice. This transformation of culture should take place at all levels of learning to enhance results.